STUDI FASIES DAN LINGKUNGAN PENGENDAPAN BATUAN KARBONAT, FORMASI WONOSARI, PADA SITUS GOA JEPANG, DAERAH PESISIR PARANGTRITIS, DESA SELOHARJO, KECAMATAN PUNDONG, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Dina Tania (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2017)
This research concerning about Facies and Sediment Environment of Carbonate Rock in Wonosari Formation. Research located at Goa Jepang site, in Parangtritis coastal areas, Seloharjo Village, Pundong Sub District, Gunungkidul District, Yogyakarta Special Region. Geographic position S 7o59’54’’-8o00’14’’ and E 110o19’43”-110o19’58”. Method of research is including rock outcrop profile and petrography thin section for three observer location in Goa 1, Goa 2, and Goa 3, from 18 location of Goa. There are 18 sites of Goa Jepang and it has three facies of stone unit, wackestone, packstone and framestone. Carbonate stone evolution for faciesof wackestone and packstone be in stabilization zone and it is placing Goa Jepang on the back reef-reef flat of depositional environment zone. However, for Goa Jepand 2nd location with framestone facies has different carbonate evolution to the diversification phase to come reef crest-reef front of depositional environment zone.